Antibacterial Activity of Marine Bacteria Associated with sponge Aaptos sp. against Multi Drugs Resistant (MDR) strains - Ocky Karna Radjasa; Duhita Sinidhikaraning Kencana; Agus Sabdono; Rory Anthony Hutagalung; Endang Sri Lestari (Institut Teknologi Bandung, 2007)
The improper and uncontrolled uses of antibiotics against pathogenic bacteria have resulted in the occurrence of MultiDrugs Resistant (MDR) strains. There is now an urgency to find alternative antibiotics to combat the MDR strains.Sponge associated microorganisms are among the most interesting and promising marine natural product sources whichproduce polyketide and non ribosomal peptide products with various biological activities. In this study, marine bacteriawere isolated from sponge Aaptos sp. collected from North Java Sea, and were screened for antibacterial activityagainst MDR strains. Three out of 64 bacterial isolates were successfully screened and were found to be active againstMDR strains, in which two isolates (SPA1 and SPA5) were active against resistant strain Escherichia coli and one isolate(SPA21) against resistant strain Proteus sp., respectively. These active isolates were also capable of amplifying NRPS(Non Ribosomal Peptide Synthetases) gene fragments necessary for the biosynthesis of non ribosomal peptides. Themolecular identification based on partial 16S DNA nukleotide sequences indicates that the active isolates areHalomonas aquamarina, Alpha proteobacterium, and Pseudoalteromonas luteviolacea.